Lestari Adventure : Sistem Digital untuk Persewaan Alat Outdoor dan Pemesanan Porter Berbasis Web - Yosua Sandy Istianto; Danar Endiarso; Arya Muzaqqi Irsyad; Muhammad Wildan Ashari (Lembaga Pengembangan Kinerja Dosen, 2025)
Lestari Adventure offers a modern solution for outdoor equipment rental and porter services in Indonesia, combining efficiency and convenience in a single web-based platform. Previously, many outdoor enthusiasts faced difficulties in booking equipment and porters separately, which often led to delays, price overruns, and a lack of transparency. With this platform, users can easily book goods and services in an integrated system, streamlining communication between renters, porters, and administrators. The system is designed with a user-friendly dashboard that allows renters to select the equipment they need, check availability, and communicate directly with available porters. Integrated inventory management features allow administrators to monitor stock in real time and avoid overbooking or understocking. Furthermore, Lestari Adventure is equipped with a secure online payment system, providing convenience for renters and administrators. PIECES analysis of this system shows significant improvements in several aspects. System performance has seen faster transaction processing times, better control over inventory and reservations, and increased user satisfaction thanks to easy access and price transparency. Lestari Adventure is expected to expand its service reach to more regions in Indonesia, address logistical challenges, and support the development of ecotourism and outdoor activities that are increasingly accessible to the public. With its comprehensive features and easy access, Lestari Adventure has the potential to transform the way outdoor enthusiasts plan and execute their activities. Furthermore, the platform also provides opportunities for local porters to increase their income through a more structured and transparent booking system.